Learning Management in Special Sports Junior High School in Surakarta - Purnomo, Shodiq; Haryanto, Sigit; Darsinah, D (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: In order to better understand how special sports schools in Surakarta implement learning management at the junior high school level, this study concentrates on three key areas: (1) learning planning; (2) classroom/field learning implementation; and (3) evaluation implementation. Methodology: The method used in this study is qualitative. Observations, interviews, and documentation are some of the methods used to gather data. Results: The analysis results show that the learning management carried out by the school includes four stages, namely (1) learning planning, (2) implementation of learning in the classroom/field, and (3) evaluation implementation. In principle, the school has implemented that management. The implementation of lesson planning, from creating mapping to making lesson plans, has been carried out even though only photocopies made by the subject teacher working group (MGMP) were used. The implementation of learning has also been going well, although the teachers still haven't been able to make the best use of their time. In conducting evaluations, many teachers still focus on evaluating outcomes rather than the evaluation process, so these evaluations tend to measure achievements rather than the success of the learning implementation. Applications/Originality/Value: The suggestions that can be given are: the principal should require teachers to write their lesson plans by hand, the school should, if necessary, reward teachers who diligently carry out their duties, and for the teachers, it is hoped that they will always adhere to all established rules so that they can enjoy their duties more.